Health-related quality of life and physical activity in Ukrainian pediatric patients with heterozygous familial hypercholesterolemia - Yе.-E.В. Kulchytska; T.V. Marushko; T.V. Kurilina (Group of Companies Med Expert, LLC, 2023)
Introduction. Familial hypercholesterolemia (FH) is a genetically determined disease characterized by elevated low-density lipoprotein levels since birth and predisposes a person to develop atherosclerosis-induced cardiovascular disease. Healthcare providers should monitor the health status and physical activity level in pediatric patients with FH, as a high-risk group for cardiovascular disease. Purpose - to investigate the self-reported health-related quality of life (HRQoL) and physical activity energy expenditure based on the questionnaire data (PAEEq) in children with heterozygous FH compared with healthy peers to assess the health status. Materials and methods. The HRQoL scores were assessed using the KINDLR questionnaire in 15 patients with FH and 21 healthy peers. The physical activity level was evaluated using the C(Y)PAQ questionnaire. The KINDLR data together with other variables such as age, weight, height, sex, BMI and the PAEEq scores were analyzed in SAS® OnDemand for Academics. Results. HRQoL scores in FH children were similar to those of the control group (p>0.05). There was no association between PAEEq and the HRQoL scores in the FH (r=0.37, p=0.29) and the control group (r=0.43, p=0.20). The KINDLR Physical well-being score in the 5-9 years age group was significantly higher for FH children than for controls (p<0.01), while the total HRQoL score was not significantly different between FH children and controls. The group of FH children aged 5-9 with an intermediate level of PAEEq was the most physically active among the surveyed children. The controls aged 15-18 with low levels of PAEEq was the least active. All other age groups were characterized by a low intermediate level of PAEEq. Conclusions. Children with FH have HRQoL scores that are comparable to those of healthy peers. The FH and control groups were relatively satisfied with their quality of life. Thus, FH children consider themselves to be healthy, and from this underestimation of their cardiovascular risk they may have low adherence. Most FH children were found to have the low intermediate levels of PAEEq, which may indicate a lack of exercise and poor quality of life later on. Children with FH may have significant health problems in adulthood if they are not treated early and appropriately. In a similar manner, low PAEEq levels were demonstrated by the controls, so they should be also informed about the significance of regular physical activity and properly motivated. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee of the participating institution. The informed consent of the patients was obtained for conducting the studies. No conflict of interests was declared by the authors.